Designing for empowerment impact in agricultural development projects: Experimental evidence from the Agriculture, Nutrition, and Gender Linkages (ANGeL) project in Bangladesh - Quisumbing, Agnes R.; Ahmed, Akhter; Hoddinott, John F.; Pereira, Audrey; Roy, Shalini (International Food Policy Research Institute, 2020)
The importance of women’s roles for nutrition-sensitive agricultural projects is increasingly recognized, yet little is known about whether such projects improve women’s empowerment and gender equality. We study the Agriculture, Nutrition, and Gender Linkages (ANGeL) pilot project, which was implemented as a cluster-randomized controlled trial by the Government of Bangladesh. The project’s treatment arms included agricultural training, nutrition behavior change communication (BCC), and gender sensitization trainings to husbands and wives together – with these components combined additively, such that the impact of gender sensitization could be distinguished from that of agriculture and nutrition trainings. Empowerment was measured using the internationally-validated project-level Women’s Empowerment in Agriculture Index (pro-WEAI), and attitudes regarding gender roles were elicited from both men and women, to explore potentially gender-transformative impacts. Our study finds that ANGeL increased both women’s and men’s empowerment, raised the prevalence of households achieving gender parity, and led to small improvements in the gender attitudes of both women and men. We find significant increases in women’s empowerment scores and empowerment status from all treatment arms but with no significant differences across these. We find no evidence of unintended impacts on workloads and we note inconclusive evidence of possible increases in intimate partner violence (IPV). Our results also suggest some potential benefits of bundling nutrition and gender components with an agricultural development intervention; however, many of these benefits seem to be driven by bundling nutrition with agriculture. While we cannot assess the extent to which including men and women within the same treatment arms contributed to our results, it is plausible that the positive impacts of all treatment arms on women’s empowerment outcomes may have arisen from implementation modalities that provided information to both husbands and wives when they were together. The role of engaging men and women jointly in interventions is a promising area for future research.